Strategi Komunikasi Politik Tim Kampanye Presiden Jokowi-Ma’ruf Amin Untuk Memperoleh Dukungan Pemilih Umat Islam Pada Pemilu 2019 Di Provinsi Sumatera Utara - Muhammad Idris (Jurnal Penelitian dan Ilmu-Ilmu Keislaman, 2019)
For each campaign team or winning body, the goal of the campaign is to win. How thestrategy that was designed succeeded in bringing the pair of candidates who were promotedto occupy the positions contested through the direct election mechanism by the people. Forthe general election community is a means for the people to choose leaders who areconsidered capable of bringing progress to the people, nation and state. The correct electionmoment determines the future of the nation, progress and prosperity for the Indonesianpeople going forward. Here the researcher is interested in exploring, analyzing, studying, andsharpening how the political communication strategy carried out by the Regional CampaignTeam (TKD) of North Sumatra Province, presidential pair Jokowi-Ma'ruf Amin, in gainingvoter support and the 2019 election victory in North Sumatra Province